DEVELOPING ESSAY WRITING SKILLS IN WELCOMING THE INDUSTRIAL REVOLUTION 4.0 TO SUPPORT LITERACY POSITION INDONESIAN NATION - DR. HINDUN (International Journal of Innovations in Engineering Research and Technology, 2021)
Not everyone likes to write. Posts that are popular with audiences are also various types. From light to heavy content, fiction and nonfiction types to writing that is more dominated by images such as "comic" (pictorial stories) or dialog filled text (text or drama scripts). An issue that is dealt with in passing in a prose essay based on the author's personal point of view is called Essay. Essay writing requires writing skills with a mastery of content accompanied by opinions, of course using the right grammar. Language that is good and true and acceptable to readers becomes the most important part of writing skills. Therefore, writing as a supreme skill in the order of language skills becomes an indispensable thing in compiling an essay. The purpose of this paper is to describe essay writing skills among students as an illustration of high-level skills in Indonesian. Descriptive qualitatively, the researcher will inform the reader of concrete forms of essay writing skills in terms of the suitability of the themes, main ideas / ideas, arguments, and writing / grammar used. Through a study that focuses on discussions around the 2030 SDGs (Sustainable Development Goals), the researcher knows the students' thoughts in the form of opinions that are aligned with the seventeen goals of the SDGs 2030 namely five objectives namely goals number 4, 5, 9, 11, and 16.